Baseline Hepatitis B Virus Titer Predicts Initial Postpartum Hepatic Flare: A Multicenter Prospective Study. Issue 10 (November 2018) - Liu, Jinfeng; Wang, Jing; Qi, Caijing; Cao, Furong; Tian, Zhen; Guo, Dandan; Yan, Taotao; Li, Qian; Yang, Shujuan; Fu, JianJun; Tang, Xianmei; Kou, Xiaoni; et al.
Abstract : Background and Goals: A series of changes in the immune system occur during pregnancy and puerperium. Currently, we aim to characterize both the natural changes in liver inflammation and its association with hepatitis B viremia during this special period. Patients and Methods: Chronic hepatitis B (CHB) gravidas were recruited and followed up to 52 weeks postpartum. Virological and biochemical parameters were assessed throughout the period. Results: A total of 1097 CHB mothers had finished the entire follow-up including 451 accepting telbivudine, 178 accepting tenofovir, and 468 without antiviral therapy. Among the mothers, 11.94% went through hepatic flare in the first trimester and the rate decreased to 2.1% at the time of delivery. Nevertheless, a much higher frequency (19.78%) was observed in the early postpartum. Interestingly, alanine aminotransferase level decreased along with the development of pregnancy and then suddenly increased in the first month of puerperium. In addition, a downward trend was observed on the titer of HBsAg and HBeAg after delivery. Of note, an obvious higher frequency of alanine aminotransferase flare was revealed in mothers with high viremia (>6 log10 IU/mL). With multivariate analysis, only hepatitis B virus titer at baseline was strongly associated with hepatic flare during early postpartum (95% confidence interval, 1.012-3.049, P =0.045). The predictive rates of hepatic flare at baseline viral load of 6, 7, and 8 log10 IU/mL were 16.67%, 28.30%, and 30.60%, respectively. Conclusions: CHB gravidas with high viremia should be monitored closely during entire pregnancy, and extended antiviral therapy is recommend to those mothers with baseline viremia >7 log10 IU/mL.